1991
DOI: 10.1063/1.460693
|View full text |Cite
|
Sign up to set email alerts
|

The 3←0 CH stretch overtone of benzene: An optothermal study

Abstract: The second CH stretch overtone of benzene at the rotational temperature of about 20 K has been measured in a supersonic molecular beam. Infrared absorption has been detected by means of the optothermal method. At least seven vibrational bands have been resolved in the wave numbers range from 8740 to 8870 cm−1. The main absorption peak is located around 8827 cm−1, but a significant absorption is observed also in ‘‘red’’ region of the spectrum, around 8770 cm−1. Experimental spectra have been compared with a the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 21 publications
4
23
0
Order By: Relevance
“…The shift is larger in the compound with two fluorine substituents on the ring. A similar relationship between aryl CH stretching frequency and the number of fluorine substituents in benzene was described by Gough and Henry1 5 . Part of the blue shift comes from the higher fundamental frequencies in the fluorinated pyridines.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…The shift is larger in the compound with two fluorine substituents on the ring. A similar relationship between aryl CH stretching frequency and the number of fluorine substituents in benzene was described by Gough and Henry1 5 . Part of the blue shift comes from the higher fundamental frequencies in the fluorinated pyridines.…”
Section: Resultsmentioning
confidence: 64%
“…It is possible that fluorination eliminates one of the three CH local modes and splits the remaining two which were previously unresolved in the spectrum of pyridine. Gough and Henry 1 5 reported that in fluorobenzene the ortho CH stretch absorptions shifted to the blue further than the meta and para CH absorptions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In that context excited electronic states and their radiationless transitions have been discussed in detail [4][5][6][7] and also intramolecular dynamics in the electronic ground state [8][9][10][11][12][13][14][15][16][17] (for further references see [17]). …”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] The second overtone state CH(vϭ3) in benzene has been the object of numerous studies, both experimentally and theoretically. [9][10][11][12][13][14][15][16][17][18][19][20] From their gas phase photoacoustic spectrum of the CH(vϭ3) state, Reddy, Heller, and Berry 10 inferred a homogeneous intramolecular vibrational redistribution ͑IVR͒ bandwidth of ϳ23 cm Ϫ1 and pronounced nonstatistical ͑nonergodic͒ redistribution character. Later Page, Shen, and Lee, 12 using state selective multilevel saturation spectroscopy of rotationally jet-cooled molecules (T rot ϳ5 K) observed a central peak of 10 cm Ϫ1 width.…”
Section: Introductionmentioning
confidence: 99%